Viability of microbial mass in a submerged membrane bioreactor - Hasar, H; Kinaci, C; Unlü, A (Elsevier, 2002)
In this study the viability of biomass in a submerged membrane activated sludge system (sMBR) which treats domestic wastewater was investigated by dealing with non-biodegradable COD, specific oxygen uptake rate and MLVSS during operation for 100 days. It was shown that the viability of biomass in the bioreactor was reduced at the 50% level because of the accumulation of inert compounds and the reduction in the activities of poor biomass. After inoculating the bioreactor again, the specific OUR increased because of young biomass entering into the bioreactor. It was shown that there was an exponential relationship between OUR and MLVSS and there was a logarithmic relationship between specific OUR and MLVSS.
Keywords: activated sludge; submerged membrane; domestic wastewater; treatment